2023
DOI: 10.3389/fmicb.2022.1069964
|View full text |Cite
|
Sign up to set email alerts
|

Effects of milk replacer feeding level on growth performance, rumen development and the ruminal bacterial community in lambs

Abstract: Feeding with a suitable level of milk replacer (MR) can improve the survival rate and stimulate the growth potential of early lambs. However, feeding excessive MR might be detrimental to rumen development and microbial colonization. Herein, we investigated the effects of feeding different levels of MR on rumen digestive function and ruminal microorganisms. Fourteen healthy male Hu lambs with similar birth weights and detailed pedigree records were divided into two groups to receive low (2% of average body weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…Although there was no significant difference in DM intake after weaning, lambs in group H tended to exhibit lower ADG and higher FCR than those in group C, which may be because the lambs in group H were more susceptible to weaning stress. Studies have shown that weaning stress can be recovered in the short term, and the adverse effects do not usually last long [5,22].Moreover, research has indicated that intensive MR feeding has detrimental effects on rumen development [6], which could be a contributing factor to the temporary decline in growth performance observed in lambs after weaning. Nevertheless, we found that high MR feeding levels improved the intestinal digestive enzyme activity and tissue morphological development in lambs, and this effect was still observed 14 days postweaning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there was no significant difference in DM intake after weaning, lambs in group H tended to exhibit lower ADG and higher FCR than those in group C, which may be because the lambs in group H were more susceptible to weaning stress. Studies have shown that weaning stress can be recovered in the short term, and the adverse effects do not usually last long [5,22].Moreover, research has indicated that intensive MR feeding has detrimental effects on rumen development [6], which could be a contributing factor to the temporary decline in growth performance observed in lambs after weaning. Nevertheless, we found that high MR feeding levels improved the intestinal digestive enzyme activity and tissue morphological development in lambs, and this effect was still observed 14 days postweaning.…”
Section: Discussionmentioning
confidence: 99%
“…The intensive use of MRs can reportedly promote lamb weight gain and improve immunity; however, at the same time, it can reduce the starter intake, which is not conducive to rumen development [5,6]. Furthermore, nutrients required for optimal growth performance in young animals may not be the same as those required for optimal intestinal development and healthy immune system maintenance [7].…”
Section: Introductionmentioning
confidence: 99%
“…Lopes et al [9] found that Nellore cattle with high feed efficiency exhibited a relatively high abundance of Anaerotruncus, Phocaeicola, unclassified Prevotella, and lower levels of Bacteroidetes during the growth stage. High-growth performance Yak calves [10] and lambs [11] with milk replacer feeding were highly enriched in the Prevotella and Christenselelaceae_R-7_group. The enrichment of Sediminibacterium and Butyrivibrio in the intestine can promote weight gain in weaned piglets, as shown in previous studies [12].…”
Section: Introductionmentioning
confidence: 99%